Electroluminescence from a quantum-well LED using NEGF - Steiger, Sebastian; Veprek, Ratko G.; Witzigmann, Bernd (Proceedings - 2009 13th International Workshop on Computational Electronics, IWCE 2009, 2009)
Nonequilibrium Green's Functions (NEGF) are employed to model carrier transport and luminescence in a single-quantum-well light-emitting diode (LED). The sound theoretical formalism allows for a consistent description of coherence loss as well as fundamental scattering mechanisms and reveals details about physical phenomena such as the quantum-confined Stark and Franz-Keldysh effects, tunneling and carrier capture. A comparison to semiclassical results is made and similarities as well as differences are highlighted. ©2009 IEEE.
CRIS-Team Scopus Importer:2021-06-11